Hydrology Modelling-Based Biopore Infiltration Holes (BIH) Determination as River Flood Disaster Mitigation in Sewu Village, Surakarta, Central Java, Indonesia - Safriani, Eka Wulan; Halimah, Anisaa Nur; Wibowo, Yunus Aris (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2020)
Sewu Village is annually experience by river flooding. The application of Biopore Infiltration Holes (BIH) is one of the measures to reduce river flood disaster risk. This research was aimed to determine the proper location of the BIH. Hydrology tools by using flow direction analysis was used to obtain the best place of BIH. It utilized Digital Elevation Model (DEM), existing landuse and morphologyÃ‚Â  analysis to know the river flooding prone area and to identify the potential flow direction of surface water (run off). The conformity of those data can be used as determination of BIH. Moreover, the number of BIH had been obtained from flow direction analysis where the lower ground elevation was the best place to arrange BIH. Overall, the flood disaster risk in Sewu Village can be potentially overcome by using BIH.